Is Helicobacter pylori infection associated with nonalcoholic fatty liver disease in individuals undergoing bariatric surgery? Cross-sectional study - Cazzo, Everton (2023)
BACKGROUND: A possible direct link between nonalcoholic fatty liver disease (NAFLD) and Helicobacter pylori (H. pylori) infection has recently emerged. OBJECTIVE: This study aimed to analyze associations between the presence of histologically demonstrated NAFLD aspects with H. pylori infection in individuals with obesity undergoing bariatric surgery. DESIGN AND SETTING: An observational analytical cross-sectional study was conducted based on data collected from the medical records of individuals undergoing bariatric surgery at a tertiary university hospital in 2019. METHODS: NAFLD was assessed through histological examination of wedge liver biopsies collected during the proceedings. H. pylori infection was analyzed through the association of the urease test and histological examination performed in biopsies routinely collected during preoperative esophagogastroduodenoscopy. RESULTS: Of the 88 participants, 85% were female, and the average age was 39.1 ± 8.4 years. H. pylori infection was present in 61.4% of the patients. The mean body mass index was 36.6 ± 3.4 kg/m2. The most prevalent histopathological aspects of NAFLD were macrovesicular steatosis (92%), hepatocellular ballooning (92%), lobular inflammation (93.2%), portal inflammation (96.6%), and fibrosis (93.2%). No histopathological aspect of NAFLD was found to be significantly associated with H. pylori infection. CONCLUSION: In this study population, H. pylori infection was not significantly associated with the histopathological aspects of NAFLD in individuals with obesity undergoing bariatric surgery.